Compressive strength and compressive fatigue limit of conventional and high viscosity posterior resin composites - Brandão, Letícia; Adabo, Gelson Luis [UNESP]; Vaz, Luís Geraldo [UNESP]; Saad, José Roberto Cury [UNESP] (Sociedade Brasileira de Pesquisa Odontológica - SBPqO, 2005)
The purpose of this study was to compare the compressive strengths and compressive fatigue limits of three posterior composite resins (Filtek P-60, Surefil and Prodigy Condensable) and a universal restorative composite (Z-100). Cylindrical specimens (8 mm in length x 4 mm in diameter) were used. The dynamic test was performed using the staircase method, and the ratio between compressive fatigue limit and compressive resistance was also calculated (n = 15). The compressive strength and compressive fatigue limit data were analyzed by Anova and Tukey’s test. The Z-100 composite demonstrated higher compression strength (307.20 MPa) than Surefil (266.93 MPa) and Prodigy Condensable (222.08 MPa). The resistance of Filtek P-60 (270.44 MPa) was similar to the resistances of Z-100 and Surefil, while Prodigy Condensable presented the lowest compressive strength. In the compressive fatigue limit tests, Filtek P-60 demonstrated a higher value (184.20 MPa) than Prodigy Condensable (155.50 MPa). Surefil (165.74 MPa) and Z-100 (161.22 MPa) presented limits similar to those of Filtek P-60 and Prodigy Condensable. The compressive fatigue limit/compressive strength ratio was 70.01% for Prodigy Condensable, 68.11% for Filtek P-60, 62.09% for Surefil and 52.48% for Z-100. It was concluded that the Z-100 universal composite was more sensitive to the dynamic test than the high viscosity materials.

O objetivo deste estudo foi comparar a resistência à compressão e o limite de fadiga compressiva de três resinas compostas indicadas para dentes posteriores (Filtek P-60, Surefil e Prodigy Condensable) e uma universal (Z-100). Corpos-de-prova cilíndricos (8 mm de altura x 4 mm de diâmetro) foram usados. O teste dinâmico foi realizado usando-se o método escada e a relação entre limite de fadiga compressiva, e resistência à compressão também foi calculada (n = 15). Os dados de resistência à compressão e de limite de fadiga compressiva foram submetidos à Anova e ao teste de Tukey. O compósito Z-100 apresentou maior resistência à compressão (307,20 MPa) que Surefil (266,93 MPa) e Prodigy Condensable (222,08 MPa). A resistência de Filtek P-60 (270,44 MPa) foi similar à de Z-100 e à de Surefil, enquanto Prodigy Condensable apresentou a menor resistência à compressão. No teste de limite de fadiga compressiva, Filtek P-60 mostrou maior valor (184,20 MPa) que Prodigy Condensable (155,50 MPa). Os compósitos Surefil (165,74 MPa) e Z-100 (161,22 MPa) mostraram-se similares a Filtek P-60 e Prodigy Condensable. A relação limite de fadiga compressiva/resistência à compressão foi de 70,01% para Prodigy Condensable, 68,11% para Filtek P-60, 62,09% para Surefil e 52,48% para Z-100. Foi concluído que o compósito universal Z-100 foi mais sensível ao teste dinâmico que os materiais de alta viscosidade.
Resistência a compressão e limite de fadiga compressiva de resinas compostas convencional e de alta viscosidade para dentes posteriores
Keywords: Composite resins; Physical properties; Resinas compostas; Propriedades físicas